2010
DOI: 10.1007/s00330-010-1908-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect on renal function of an iso-osmolar contrast agent in patients with monoclonal gammopathies

Abstract: The use of iodixanol appears to be safe in patients with monoclonal gammopathies and an eGFR≥ 60 ml/min/1.73 mq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…18 This may be attributed to factors associated with cardiac angiography but not with peripheral aministration of contrast agents. Preda et al studied the effect of an iso-osmolar contrast agent on renal function in patients with monoclonal gammopathies and in patients with oncological disease 19 and found no statistically significant difference in serum creatinine, creatinine clearance and urinary NGAL levels 2 h after the procedure compared to baseline. On the other hand, a review showed the paucity of controlled clinical studies that demonstrate renal damage caused by intravenous contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…18 This may be attributed to factors associated with cardiac angiography but not with peripheral aministration of contrast agents. Preda et al studied the effect of an iso-osmolar contrast agent on renal function in patients with monoclonal gammopathies and in patients with oncological disease 19 and found no statistically significant difference in serum creatinine, creatinine clearance and urinary NGAL levels 2 h after the procedure compared to baseline. On the other hand, a review showed the paucity of controlled clinical studies that demonstrate renal damage caused by intravenous contrast agents.…”
Section: Discussionmentioning
confidence: 99%
“…Other potential clinical risk factors include hypertension, congestive heart failure, use of diuretics or NSAIDs, advanced age, hyperuricemia, and the dose of contrast administered [6••, 16]. Multiple myeloma and other monoclonal gammopathies are a risk factor with the use of HOCM [6••], but have not been linked to the newer lower-osmolality iodinated agents [21]. A second contrast-enhanced study within a short time interval from the first study may be associated with additional risk of CIN [22].…”
Section: Iodinated Contrast Agents and Contrast-induced Nephropathymentioning
confidence: 99%
“…48,49,57 Nephropathy or Nephrotoxicity Throughout the literature, patient NGAL level has been shown to be an early marker of nephropathy/nephrotoxicity in a wide spectrum of clinical conditions, including renal tubular disease, 23,65,101 systemic lupus erythematosus, 94,96 acute renal impairment, 97 CKD, 32,53,95,100 HIV-associated nephropathy, 27 sickle cell nephropathy, 102 kidney cancer, 93 and CIN. 6,22,56,59,62,138,174,175 Contrast-induced nephropathy, often defined as an increase in patient serum creatinine level by 25% to 50% above baseline and generally occurring within the first 24 hours after contrast exposure (in the absence of other causes), has become the third leading cause of nosocomial AKI. 176 The reported incidence of CIN ranges from 0 to 50%, depending on the absence or presence of risk factors.…”
Section: Cardiac Surgerymentioning
confidence: 99%
“…179 As the utility of patient NGAL level has been established in detecting AKI, it has also been investigated to determine its usefulness as an early marker of AKI associated with CIN. 62,138,174,175 Patient NGAL level has been investigated to determine its role as a potential indicator of nephropathy or nephrotoxicity. 22,56, 59 We identified 26 clinical trials meeting our inclusion criteria that investigated the role of NGAL level in nephropathy or nephrotoxicity.…”
Section: Cardiac Surgerymentioning
confidence: 99%